Предмет: Алгебра,
автор: Maox
С полным решением пожалуйста
Приложения:
Ответы
Автор ответа:
0
(c^-5 * (c^-4)^3) / c^-19 = (c^-5 * c^-12)/ c^-19 = c^-17/c^-19 = 1/c^-2 = c^2.
Автор ответа:
0
c^(-5) • c^(-12) c^(-17)
-------------------- = ---------- = c^2
c^(-19) c^(-19)
-------------------- = ---------- = c^2
c^(-19) c^(-19)
Похожие вопросы
Предмет: Алгебра,
автор: KiK233145
Предмет: Немецкий язык,
автор: Лера20165
Предмет: Биология,
автор: bershka856
Предмет: Математика,
автор: irinavladimirb
Предмет: Математика,
автор: Zhanya2005